Peculiarities of Linguistic Situation of Multinational Guiana - V. A. Kozhemyakina (Научный диалог)
The analysis of the sociolinguistic situation in Guiana, an overseas department and a region of France is presented in the article. The history of the settlement of this territory by speakers of different languages is considered. An overview of the demolinguistic situation in the region is presented, statistical data of the latest population censuses are given. A review and analysis of the results of anthropological, linguistic and sociolinguistic surveys conducted by French scientists in Guiana at the end of the 20th and the first decades of the 21st centuries is made. The novelty of the study is seen in the fact that the linguistic situation is considered simultaneously with the analysis of existing laws on languages, since only adopted laws can allow members of the linguistic community to assert and protect their rights. Particular attention is paid to the use of the Guianan Creole and French languages in various social and communicative areas: in the institutions of executive power, in the main area of the functioning of the language — the education system, in the areas of trade and the media. The relevance of the article is due to the special attention of the Russian and world community to the language situation and the solution of language problems in multi-ethnic states, as well as to the preservation of indigenous languages.